Satellite integrated communications networks : proceedings of the Third Tirrenia International Workshop on Digital Communications, Tirrenia, Italy, 14-16 September 1987 - Tirrenia International Workshop on Digital Communications (3rd : 1987 : Tirrenia, Italy); Del Re, Enrico; Bartholome, Pierre; Nuspl, Peter P. (Amsterdam : Elsevier Science, 1988)
13